2003
DOI: 10.1038/nature01444
|View full text |Cite
|
Sign up to set email alerts
|

Water transport in plants obeys Murray's law

Abstract: The optimal water transport system in plants should maximize hydraulic conductance (which is proportional to photosynthesis) for a given investment in transport tissue. To investigate how this optimum may be achieved, we have performed computer simulations of the hydraulic conductance of a branched transport system. Here we show that the optimum network is not achieved by the commonly assumed pipe model of plant form, or its antecedent, da Vinci's rule. In these representations, the number and area of xylem co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
416
2
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 396 publications
(454 citation statements)
references
References 18 publications
28
416
2
2
Order By: Relevance
“…This vertical tapering and developmental changes may be similar to those already documented for the xylem (e.g. Anfodillo et al, 2004;Mencuccini et al, 2007;McCulloh et al, 2003;West et al, 1999), at least partially. In the xylem, conduit tapering is predicted to reduce the adverse effects of growing transport distance on the whole xylem pathway conductance (West et al, 1999).…”
Section: Different Phloem Construction Criteriasupporting
confidence: 87%
“…This vertical tapering and developmental changes may be similar to those already documented for the xylem (e.g. Anfodillo et al, 2004;Mencuccini et al, 2007;McCulloh et al, 2003;West et al, 1999), at least partially. In the xylem, conduit tapering is predicted to reduce the adverse effects of growing transport distance on the whole xylem pathway conductance (West et al, 1999).…”
Section: Different Phloem Construction Criteriasupporting
confidence: 87%
“…This matches model simulations of leaves where increasing major vein density led to a linear decrease in xylem resistance (McKown et al 2010). Decreasing r * LV through changes in the number of vascular bundles rather than the size of vessel elements is expensive to plants as cost of xylem construction is fairly high (McCulloh et al 2003). We found no significant correlations between any anatomical characteristics (D m or vein density) and r * OLV , which suggests that the hydraulic resistance outside the large longitudinal veins may have been controlled by other mechanisms.…”
supporting
confidence: 64%
“…20 Also, it has been shown that most of the branching systems in the nature such as vasculatures and plants obey Murray's law. [21][22][23] Murray's law is also in agreement with the constructal theory which states "For a finite-size flow system to persist in time (to survive) its configuration must evolve (morph) in time in such a way that it provides easier flow access to its currents". 24 Moreover, some studies have tried to generalize Murray's law to obtain a general rule for designing microfluidic networks.…”
Section: Introductionsupporting
confidence: 51%